Intensive methods of teaching foreign languages (in Spanish example) - Sabirova, Nilufar (The Lingua Spectrum, 2024)
This article describes the methodology of teaching foreign languages, the history and stages of their development, modern methods and their types used today in teaching foreign languages, and ways of using them. In today's developing era, changes and significant progress occur in all areas, especially in the field of science. After our country gained independence, attention to science, especially foreign languages, increased. Teaching each subject using modern innovative technologies and methods is one of the most important requirements of the modern era. Effective use of modern pedagogical technologies and methods in each lesson in the learning process helps students to think independently and freely, to search, to take a serious approach to each issue, to strengthen interest in learning, which allows achieving positive results.